Electrode for lithium ion secondary battery and lithium ion secondary battery
Patent Information
- Application Number
- JP2021056296
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-29
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-03-29
AI Technical Summary
【0014】 本発明によれば、リチウムイオン二次電池に外部から衝撃が加わり、内部短絡が発生しうる状況になっても、発熱を抑制しうるリチウムイオン二次電池用電極と、それを用いたリチウムイオン二次電池を得ることができる。
Smart Images

Figure 0007640331000002 
Figure 0007640331000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode for a lithium ion secondary battery and a lithium ion secondary battery. [Background technology]
[0002] Lithium-ion secondary batteries are widely used as power sources for portable electronic devices because they are lighter and have a higher energy density than nickel-cadmium batteries, nickel-metal hydride batteries, etc. They are also a promising candidate for use as power sources in hybrid and electric vehicles. As portable electronic devices have become smaller and more sophisticated in recent years, there is a demand for lithium-ion secondary batteries, which serve as the power sources for these devices, to have even higher energy densities.
[0003] Although the current lithium ion secondary battery has a high level of safety, further improvement in safety is required due to its high capacity and high output. For example, if the lithium ion secondary battery is overcharged, it may generate heat. Also, it may generate heat due to the occurrence of an internal short circuit. Furthermore, since the lithium ion secondary battery contains a non-aqueous electrolyte containing an organic solvent, the organic solvent may chemically decompose with heat generation, generating gas, which may cause problems such as an increase in the internal pressure of the battery.
[0004] To address such problems, Patent Document 1 proposes a technique of providing a conductive layer having a PTC function on the surface of a current collector. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2014 / 050653 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the current collector provided with the conventional conductive layer having the PTC function described in Patent Document 1 had a problem in that it was insufficient as a countermeasure against heat generation caused by an internal short circuit due to an impact. As a result of extensive research, the present inventors discovered that this was due to the fact that the shell layer forming the conductive layer was difficult to detach from the core particle when an impact was applied.
[0007] The present invention has been made in view of the above problems, and has an object to provide an electrode that suppresses heat generation due to an external impact on a lithium ion secondary battery. [Means for solving the problem]
[0008] In order to achieve the above-mentioned object, the electrode for a lithium ion secondary battery of the present invention comprises a metal foil, a conductive layer formed on at least a part of the metal foil, and an active material layer formed on at least a part of the surface of the conductive layer opposite the surface facing the metal foil, wherein the conductive layer has composite particles composed of inorganic particles and conductive particles, and the composite particles have the conductive particles on at least a part of the surface of the inorganic particles.
[0009] In the lithium ion secondary battery electrode according to the present invention, when an impact is applied to the lithium ion secondary battery, the conductive particles are detached from the composite particles constituting the conductive layer, exposing the inorganic particles. At this time, the conductive layer functions as a resistance layer due to the electrical resistance of the inorganic particles. Therefore, it is possible to suppress internal short-circuiting in the lithium ion secondary battery and the heat generation caused by the short-circuiting.
[0010] The inorganic particles are preferably made of a lithium compound.
[0011] In addition to being stable in the electrolyte, it is important that the conductive layer is easy to remove the conductive particles when the lithium ion secondary battery is subjected to an impact. If the hardness is too low, the impact on the conductive particles is absorbed, making it difficult for the conductive particles to be removed from the inorganic particles, and if the hardness is too high, the conductive particles are difficult to stretch, so that the conductive particles are also difficult to remove from the inorganic particles. With this configuration, the lithium compound has an appropriate hardness, and when an impact is applied, the conductive particles are easy to remove from the inorganic particles. Therefore, it is possible to further improve the effect of suppressing heat generation in the lithium ion secondary battery.
[0012] Moreover, the inorganic particles are preferably LiVOPO4.
[0013] This configuration improves the thermal stability of the inorganic particles in the conductive layer. Therefore, even if the resistance layer generates heat due to the electric potential applied thereto while the internal short circuit is suppressed, the function of the resistance layer is maintained, and the expansion of the internal short circuit and the associated temperature rise are suppressed. In addition, it is also preferable that the conductive particles have a hardness that makes them easy to remove. Therefore, the lithium ion secondary battery using the above-mentioned lithium ion secondary battery electrode can further improve the effect of suppressing heat generation. Effect of the Invention
[0014] According to the present invention, it is possible to obtain an electrode for a lithium ion secondary battery that can suppress heat generation even when the lithium ion secondary battery is subjected to an external impact and an internal short circuit may occur, and a lithium ion secondary battery using the electrode. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a schematic cross-sectional view of a laminate of a lithium ion secondary battery according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, preferred embodiments of the present invention will be described, however, the present invention is not limited to the following embodiments.
[0017] <Lithium-ion secondary battery> FIG. 1 shows a schematic cross-sectional view of a laminate of a lithium ion secondary battery according to this embodiment.
[0018] A laminate 10 of a lithium ion secondary battery can be produced by preparing a positive electrode composed of 1, 2, and 3, a negative electrode composed of 5, 6, and 7, and a separator 4 impregnated with an electrolyte as shown in FIG. 1. Here, the positive electrode can be produced by forming a positive electrode active material layer 1 on a positive electrode current collector 3 or on a conductive layer 2 provided on the positive electrode, and the negative electrode can be produced by forming a negative electrode active material layer 5 on a negative electrode current collector 7 or on a conductive layer 6 provided on the negative electrode. However, in order to exert the effect of the present invention, it is necessary to form the conductive layer 2 between the positive electrode current collector 3 and the positive electrode active material layer 1, or to form the conductive layer 6 between the negative electrode current collector 7 and the negative electrode active material layer 5. In addition, 8 and 9 in the drawing indicate the extraction electrodes of the positive electrode and the negative electrode, respectively.
[0019] <Metal foil with conductive layer> The metal foil having a conductive layer according to this embodiment is an electrode for a lithium ion secondary battery having a conductive layer formed on at least a part of one side or the entire surface thereof and an active material layer formed on the conductive layer. The conductive layer contained in this electrode is characterized by including a core particle which is an inorganic particle, and a composite particle having a conductive particle on at least a part of the surface of the core particle.
[0020] During normal use of the lithium ion secondary battery, the conductive particles on the surface of the core particle ensure a good electronic path and function as a conductive layer. On the other hand, when the lithium ion secondary battery is subjected to an external impact and an internal short circuit occurs, the conductive particles are detached from the surface of the core particle, and the electronic path is lost, so that the battery functions as a high resistance layer. Hereinafter, an embodiment required for providing the function will be described.
[0021] The metal foil of this embodiment may be any conductive plate material. For example, for the negative electrode, a thin metal plate (metal foil) of copper, nickel or an alloy thereof, stainless steel, etc. may be used, and for the positive electrode, a thin metal plate (metal foil) of aluminum or an alloy thereof, stainless steel, etc. may be used.
[0022] The inorganic particles of the present embodiment are preferably inorganic particles having a high resistance value that can suppress the generation of a large current when an internal short circuit is initiated by an external impact. 6 For example, ceramics such as alumina and zirconia, and oxides with high electrical resistance such as lithium ion compounds such as LiFePO4 and LiVOPO4 can be used.
[0023] Considering the ease of removal of the conductive particles from the surface, it is desirable that the inorganic particles have not only high resistance but also moderate hardness. That is, the ease of removal of the conductive particles from the inorganic particle surface is affected by the hardness of the inorganic particles. If the hardness of the inorganic particles is too low, external impacts tend to be absorbed inside the conductive particles, making it difficult for the conductive particles to be removed. On the other hand, if the hardness is too high, the conductive particles tend to be difficult to deform, making it difficult to form a base point that eliminates the adsorption between the inorganic particles and the conductive particles, and as a result, it tends to be difficult for the conductive particles to be removed.
[0024] The inorganic particles are preferably LiVOPO4 among lithium ion compounds. LiVOPO4 has a moderate strength among inorganic particle materials, so it is easy to form a high resistance layer, and has a secondary safety advantage of being able to maintain electrical resistance even if the temperature inside the battery rises due to an internal short circuit due to its high thermal stability.
[0025] The conductive particles of this embodiment are not particularly limited as long as they have good conductivity, and include carbon-based materials, metal fine powders such as copper, nickel, stainless steel, and iron, carbon materials, conductive oxides such as ITO, and compounds and mixtures thereof. Considering the ease of removal from the inorganic particle surface, carbon-based materials that are more flexible than inorganic particles are preferred. Examples of the carbon-based materials include carbon black, graphene, carbon nanofibers, carbon nanotubes, carbon nanowalls, and graphite.
[0026] The conductive particles may be present on at least a part of the surface of the inorganic particles, but it is preferable that they cover 50% or more of the inorganic particle surface. At the same time, it is preferable that the resistance value of a composite particle in which the conductive particles are provided on a part of the surface of the inorganic particles is 50 Ωcm or less. This tends to suppress a decrease in output during normal use of the lithium ion secondary battery.
[0027] <Measurement of Coverage Ratio of Inorganic Particles Covered with Conductive Particles> To measure the coverage of the composite particles by the conductive particles, X-ray photoelectron spectroscopy (hereinafter referred to as "XPS") can be used. That is, a spectrum derived from the inorganic particles and a spectrum derived from the conductive particles are obtained by XPS, and each component is quantified, and the quantitative value of the spectrum derived from the conductive particles can be regarded as the coverage of the inorganic particles by the conductive particles.
[0028] <Measurement of resistance value of inorganic particles coated with conductive particles> The resistance value of the composite particles is measured using a resistance meter. To measure the resistance value, the composite particles are molded into pellets, and the produced pellets are measured with the resistance meter to obtain the resistance value of the composite particles.
[0029] <Production of composite particles> The composite particles of this embodiment are manufactured by filling inorganic particles and conductive particles in a planetary ball mill, grinding and mixing, and recovering. Here, the filling amount of the inorganic particles is preferably 5 to 30 parts by mass, and more preferably 5 to 15 parts by mass, when the filling amount of the conductive particles is 1 part by mass. The filling amount of the inorganic particles and the conductive particles is such that the composite particles have a rich amount of conductive particles so as not to impair the output when normally used as a lithium ion secondary battery, and have a small amount of conductive particles so that the inorganic particles are exposed due to peeling of the conductive particles and become a high resistance layer when the lithium ion secondary battery is subjected to an impact from the outside. The above range is a preferable filling amount range that allows both functions to be exhibited.
[0030] <Formation of conductive layer on current collector> The composite particles, the conductive assistant, and the binder are mixed and dispersed in a solvent such as water or N-methyl-2-pyrrolidone to prepare a paste-like slurry. Next, the slurry is applied to one or both sides of a current collector such as aluminum foil or copper foil in a predetermined thickness using, for example, a comma roll coater, and the solvent is evaporated by introducing the slurry into a drying furnace. When the slurry is applied to both sides of the current collector, it is desirable that the thickness of the coating film that becomes the conductive layer is the same on both sides. After the solvent is evaporated, pressure molding may be performed by a roller press. The thickness of the coating film that becomes the conductive layer is preferably 1 [μm] or more and less than 10 [μm]. This makes it possible to fully function as a high resistance layer when an impact is applied to the lithium ion secondary battery from the outside and an internal short circuit may occur, and does not reduce the output during normal use.
[0031] <Positive electrode> As described below, the positive electrode can be produced by forming a positive electrode active material layer 1 on a positive electrode current collector 3 or on a conductive layer 2 provided on the positive electrode.
[0032] (Positive electrode current collector) The positive electrode current collector 3 may be any conductive plate material, and may be, for example, a thin metal plate or foil made of aluminum or an alloy thereof, stainless steel, or the like.
[0033] (Positive electrode active material layer) The positive electrode active material layer 1 is mainly composed of a positive electrode active material, a binder for the positive electrode, and, if necessary, a conductive assistant for the positive electrode in an appropriate amount.
[0034] (Positive electrode active material) As the positive electrode active material, there is no particular limitation as long as it can reversibly proceed with the occlusion and release of lithium ions, the desorption and insertion (intercalation) of lithium ions, or the doping and dedoping of lithium ions and the counter anion of the lithium ions (for example, PF6 - ), and known electrode active materials can be used. For example, lithium cobaltate (LiCoO2), lithium nickelate (LiNiO2), lithium manganese spinel (LiMn2O4), and the general formula: LiNi x Co y Mn z MaO2 (x + y + z + a = 1, 0 ≦ x ≦ 1, 0 ≦ y ≦ 1, 0 ≦ z ≦ 1, 0 ≦ a ≦ 1, M is one or more elements selected from Al, Mg, Nb, Ti, Cu, Zn, Cr), lithium vanadium compound (LiV2O5), olivine-type LiMPO4 (where M is one or more elements selected from Co, Ni, Mn, Fe, Mg, Nb, Ti, Al, Zr or VO), lithium titanate (Li4Ti5O 12) , LiNi x Co y Al z O2 (0.9 < x + y + z < 1.1), etc. of composite metal oxides can be mentioned.
[0035] (Binder for the positive electrode) The positive electrode binder binds the positive electrode active materials together and also binds the positive electrode active materials to the current collector. The binder may be any material capable of the above-mentioned bonding, such as fluororesins such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE). In addition to the above, for example, cellulose, styrene-butadiene rubber, ethylene-propylene rubber, polyimide resin, polyamide-imide resin, etc. may be used as the binder. In addition, an electronically conductive conductive polymer or an ionically conductive conductive polymer may be used as the binder. For example, polyacetylene may be used as an electronically conductive conductive polymer. In this case, the binder also functions as a conductive additive particle, so there is no need to add a conductive additive. As the ion-conductive conductive polymer, for example, one having ion conductivity such as lithium ion can be used, and examples thereof include a composite of a monomer of a polymer compound (polyether polymer compounds such as polyethylene oxide and polypropylene oxide, polyphosphazene, etc.) and a lithium salt such as LiClO4, LiBF4, LiPF6, or an alkali metal salt mainly composed of lithium. Examples of the polymerization initiator used for the composite include a photopolymerization initiator or a thermal polymerization initiator that is compatible with the above-mentioned monomer.
[0036] (Conductive assistant for positive electrode) The conductive assistant for the positive electrode is not particularly limited as long as it improves the conductivity of the positive electrode active material layer 1, and a known conductive assistant can be used. Examples of the conductive assistant include carbon materials such as graphite and carbon black, metal fine powders such as copper, nickel, stainless steel, and iron, mixtures of carbon materials and metal fine powders, and conductive oxides such as ITO.
[0037] <Negative electrode> The negative electrode can be produced by forming a negative electrode active material layer 5 on a negative electrode current collector 7 or on a conductive layer 6 provided on the negative electrode, as described below.
[0038] (Anode current collector) The negative electrode current collector 7 may be any conductive plate material, and may be, for example, a thin metal plate (metal foil) of copper, nickel, or an alloy thereof, stainless steel, or the like.
[0039] (Negative electrode active material layer) The negative electrode active material layer 5 is mainly composed of a negative electrode active material, a negative electrode binder, and a necessary amount of a negative electrode conductive assistant.
[0040] (Negative electrode active material) The negative electrode active material is graphite, silicon oxide (SiO x ), metal silicon (Si), etc.
[0041] (Negative electrode binder) The negative electrode binder is not particularly limited, and the same binder as the positive electrode binder described above can be used.
[0042] The content of the binder in the negative electrode active material layer 5 is not particularly limited, but is preferably 1 to 20 parts by mass of the entire negative electrode active material layer.
[0043] (Conductive assistant for negative electrode) The conductive assistant for the negative electrode is not particularly limited, and the same conductive assistant for the positive electrode as described above can be used.
[0044] <Electrolytes> As the electrolyte, salts such as LiPF6, LiClO4, LiBF4, LiAsF6, LiCF3SO3, LiCF3, CF2SO3, LiC(CF3SO2)3, LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(CF3CF2CO)2, LiBOB, etc. may be used. These salts may be used alone or in combination of two or more.
[0045] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to the above-described embodiments. EXAMPLES
[0046] The present invention will be described in more detail below based on examples and comparative examples, but the present invention is not limited to the following examples.
[0047] <Example 1> (Preparation of composite particles having inorganic core particles and conductive particles on at least a part of the surface of the core particles) 50 g of LiVOPO4 and 5 g of acetylene black were placed in a planetary ball mill container, and then zirconia beads were added. The mixture was milled and mixed at a rotation speed of 500 rpm for 10 minutes, and the resulting powder was then recovered to obtain composite particles having conductive particles on at least a portion of the surface of the inorganic particles.
[0048] (Formation of a conductive layer on a current collector) 90 parts by mass of the composite particles obtained by the above method, 5 parts by mass of acetylene black, 5 parts by mass of PVdF, and N-methylpyrrolidone as a solvent were mixed to prepare a slurry for forming a conductive layer. This slurry was applied to both sides of an aluminum foil with a thickness of 12 [μm] and dried at 100 [℃] to obtain a positive electrode current collector with a conductive layer with a thickness of 5 [μm].
[0049] (Preparation of positive electrode) A slurry for forming an active material layer was prepared by mixing 96 parts by mass of LiCoO2 as a positive electrode active material, 2 parts by mass of acetylene black as a conductive assistant, 2 parts by mass of PVdF as a binder, and N-methylpyrrolidone as a solvent. This slurry was applied to both sides of the positive electrode current collector on which the conductive layer was formed obtained above, dried at 100[℃], and then pressure-molded by a roller press to obtain a positive electrode having a positive electrode active material layer.
[0050] (Preparation of negative electrode) A slurry for forming an active material layer was prepared by mixing 83 parts by mass of Si as a negative electrode active material, 2 parts by mass of acetylene black as a conductive assistant, 15 parts by mass of polyamideimide as a binder, and N-methylpyrrolidone as a solvent. This slurry was applied to both sides of a copper foil with a thickness of 10 [μm], dried at 100 [℃], pressed by a roller press, and heat-treated in a vacuum at 350 [℃] for 3 hours to obtain a negative electrode having a negative electrode active material layer.
[0051] (Preparation of lithium-ion secondary batteries for evaluation) The positive electrode and negative electrode prepared above were placed in an aluminum laminate pack with a separator made of a polyethylene microporous film sandwiched between them, and a 1 M LiPF6 solution (solvent: ethylene carbonate / diethyl carbonate = 3 / 7 (volume ratio)) was injected into this aluminum laminate pack as an electrolyte, followed by vacuum sealing to prepare a lithium ion secondary battery for evaluation.
[0052] (Measurement of rate characteristics) The lithium ion secondary battery for evaluation prepared in Example 1 was charged and discharged one cycle at a current value of 0.05[C] in a thermostatic chamber at a temperature of 25[°C] using a secondary battery charge / discharge tester (manufactured by Hokuto Denko Corporation), with the voltage range set to 2.8[V] to 4.2[V], and confirmed to have a normal capacity. Similarly, after charging at a current value of 0.05[C], discharge was performed at a current value of 0.2[C] or 2[C], and the discharge capacity at each rate was obtained, and the rate characteristic (100×2[C] discharge capacity / 0.2[C] discharge capacity) was obtained. When the resistance value of the conductive layer formed on the positive electrode current collector is low, the movement of electrons at a high rate is not inhibited, and a high retention rate is shown.
[0053] (Measurement of battery surface temperature) The lithium ion secondary battery for evaluation prepared in Example 1 was charged to 4.2 [V] in a thermostatic chamber at a temperature of 25 [°C] using a secondary battery charge / discharge tester (manufactured by Hokuto Denko Corporation), and then a nail penetration test was performed. In the nail penetration test, the lithium ion secondary battery for evaluation was fixed on a phenol resin plate with a hole of 10 [mm] in diameter in a thermostatic chamber at a temperature of 25 [°C], and an iron nail of 3 [mm] in diameter and 65 [mm] in length was pierced vertically into the lithium ion secondary battery for evaluation at a speed of 10 [mm / s], penetrating 10 [mm] from the battery, and the nail was held for 3 minutes and then pulled out. The battery surface temperature was measured 30 seconds after the nail was pierced into the battery.
[0054] <Examples 2 to 18> Lithium ion secondary batteries of Examples 2 to 18 were obtained in the same manner as in Example 1, except that the material of the inorganic particles, the coverage by the conductive particles, and the thickness of the conductive layer were changed as shown in Table 1. Moreover, using the obtained lithium ion secondary batteries, the rate characteristics and the battery surface temperature of Examples 2 to 18 were measured in the same manner as in Example 1.
[0055] The evaluation results of Examples 1 to 18 are shown in Table 1. By providing a conductive layer containing inorganic particles covered with conductive particles on a positive electrode current collector as in Examples 1 to 18, a heat generation suppression effect was obtained while maintaining the rate characteristics. Furthermore, among the inorganic particles, when a lithium compound was used, a higher heat generation suppression effect was observed, and when LiVOPO4 was used, even more favorable results were observed. Furthermore, regarding the rate characteristics, good results were obtained by setting the coverage rate of the conductive particles and the conductive layer in the optimal range.
[0056] <Comparative Examples 1 and 2> Lithium ion secondary batteries of Comparative Examples 1 and 2 were obtained in the same manner as in Example 1, except that the material of the inorganic particles, the coverage by the conductive particles, and the thickness of the conductive layer were changed as shown in Table 1. In addition, using the obtained lithium ion secondary batteries, the rate characteristics and battery surface temperature of Comparative Examples 1 and 2 were measured under the same conditions as in Example 1.
[0057] The evaluation results of Comparative Examples 1 and 2 are shown in Table 1. Comparative Example 1 did not contain inorganic particles, and the conductive layer contained only conductive particles, and showed a relatively high temperature rise. Comparative Example 2 did not contain conductive particles, and did not function as a conductive layer, so the battery surface temperature was good, but showed extremely low rate characteristics.
[0058] [Table 1] [Industrial Applicability]
[0059] By providing a conductive layer on a current collector, the conductive layer containing a core particle that is an inorganic particle and a composite particle having a conductive particle on at least a portion of the surface of the core particle, it is possible to provide a lithium ion secondary battery that suppresses heat generation while maintaining rate characteristics against external impact. [Explanation of symbols]
[0060] 1... positive electrode active material, 2... conductive layer provided on positive electrode, 3... positive electrode current collector, 4... separator, 5... negative electrode active material, 6... conductive layer provided on negative electrode, 7... current collector, 8, 9... leads, 10... laminate of lithium ion secondary battery.
Claims
1. Metal foil; A conductive layer formed on at least a portion of the metal foil; An active layer is formed on at least a part of the surface of the conductive layer opposite to the surface facing the metal foil. a material layer; the conductive layer has composite particles made of inorganic particles and conductive particles, The composite particle has the conductive particle on at least a part of the surface of the inorganic particle, The electrode for a lithium ion secondary battery, wherein the inorganic particles are LiVOPO 4 .
2. An electrode for a lithium ion secondary battery as described in claim 1, wherein the conductive particles cover more than 50% of the surface of the inorganic particles.
3. The resistance value of the composite particle is 50 Ω cm or less, 3. The electrode for a lithium ion secondary battery according to claim 1, wherein the resistance value of the composite particle is measured by preparing a pellet of the composite particle and using a resistance meter.
4. An electrode for a lithium ion secondary battery described in any one of claims 1 to 3, wherein the conductive particles of the composite particles detach from the surface of the inorganic particles when subjected to an external impact sufficient to cause an internal short circuit.
5. A lithium ion secondary battery using the electrode for lithium ion secondary batteries according to any one of claims 1 to 4.
Citation Information
Patent Citations
Composite particle for electrode and electrochemical device
JP2009087682A
Composite particle for electrode and electrochemical device
JP2009187963A
Electrode for lithium-ion battery and lithium-ion battery
JP2018101624A
Electrode for lithium ion secondary battery, and lithium ion secondary battery
JP2021034158A
Lithium-ion battery
JP2023530367A